Propriedades físico-hídricas do solo e produtividade de culturas em áreas com e sem terraço - Backes, Elcio dos Santos (2023)
Erosion can lead to loss of arable land and silting up of watercourses and reservoirs and, therefore, understanding its causes helps in decision-making on actions to mitigate the occurrence of erosion and in the adoption of measures for the conservation of environments. That is why the adoption of conservationist systems, which keep the soil protected, is essential, since they aim to improve the physical, chemical and biological quality of the soil and control the agents of erosion processes. An example is the use of terracing, which aims to minimize the erosive process and is done by building terraces, which, if level, aims to segment the volume drained on the slopes of the crops and increase the infiltration of rainwater. Thus, the present work aimed to study the physical-hydric behavior of the soil in an area with terraces and in an area where the terraces were removed, and to measure the reflection of this in the productivity of soybean and corn crops in the Southwest region of Paraná. Two areas of 1.92 ha called megaplots with and without terraces were delimited, evaluating the production of soybean (2019/20 and 2020/21 harvests) and off-season corn (2021). For the physical-hydric characterization of the soils, hydraulic conductivity, total porosity, micro and macroporosity, soil and particle density, granulometric distribution, soil resistance to penetration, volumetric humidity, stability of soils were analyzed. aggregates, and crop productivity. In addition, rainfall monitoring was carried out. The soil was characterized as very clayey and, therefore, had a high particle density, characteristic of a soil rich in iron oxides. High total porosity was also detected, with macroporosity values not limiting aeration and a predominance of micropores that lead to an increase in volumetric moisture and soil density below the critical limit for very clayey soils. The hydraulic conductivity of the saturated soil and the weighted average diameter were higher in the surface layer of the soil due to the presence of macropores. Soybean productivity in the 2019/20 season did not differ between areas with and without terraces. In 2020/21, the terraced area had higher productivity. Regarding the off-season corn, no significant difference was observed. As the terraces in the assessed area were recently removed, it is still not possible to observe the influence of this practice on the physical-hydric properties of the soil and its effect on crop productivity, requiring further study.